2010
DOI: 10.1038/ajh.2009.240
|View full text |Cite
|
Sign up to set email alerts
|

Aortic PWV in Chronic Kidney Disease: A CRIC Ancillary Study

Abstract: Background Aortic PWV is a measure of arterial stiffness and has proved useful in predicting cardiovascular morbidity and mortality in several populations of patients, including the healthy elderly, hypertensives and those with end stage renal disease receiving hemodialysis. Little data exist characterizing aortic stiffness in patients with chronic kidney disease who are not receiving dialysis, and in particular the effect of reduced kidney function on aortic PWV. Methods We performed measurements of aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
5
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 196 publications
(187 citation statements)
references
References 36 publications
9
167
5
6
Order By: Relevance
“…Previously we have reported, in these same CRIC cohort study participants, the independent positive associations of age, blood glucose concentration, AfricanAmerican ethnicity, waist circumference, mean arterial BP, male gender, and the presence of diabetes with PWV, and a significant negative association with the level of kidney function (20). These same observations were strikingly similar with our dependent variable, which was the log transformed 24-hour urine protein level.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previously we have reported, in these same CRIC cohort study participants, the independent positive associations of age, blood glucose concentration, AfricanAmerican ethnicity, waist circumference, mean arterial BP, male gender, and the presence of diabetes with PWV, and a significant negative association with the level of kidney function (20). These same observations were strikingly similar with our dependent variable, which was the log transformed 24-hour urine protein level.…”
Section: Discussionsupporting
confidence: 77%
“…Aortic pulse wave measurements were performed the same day as the BP measurements (20). These were performed supine after at least 5 minutes of rest, using the right carotid and right femoral arteries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic PWV was measured in CRIC participants at the year-2 follow-up visit and then every other year thereafter. The protocol for measuring PWV has been described previously (26). For the purposes of these analyses, PWV measurements were selected on the basis of the following priority: (1) within 30 days of the ABPM, (2) next PWV measurement after ABPM, and (3) most recent PWV measurement before ABPM.…”
Section: Study Outcomes-target Organ Damagementioning
confidence: 99%
“…Carotid to femoral pulse wave velocity (PWV) is a simple and reproducible method to measure aortic stiffness, and is highly predictive of cardiovascular mortality in patients with end‐stage renal disease10 and kidney transplant and CKD,3, 11 which is remarkable in the absence of predictive equations in these populations. We and others have shown that not only aortic stiffness but also internal diameter enlargement, thinning of the arterial wall, increased circumferential wall stress, and reduction of the arterial distensibility occur early during CKD and progress in parallel with the fall in renal function and influence prognosis 1, 2, 3, 4, 12…”
Section: Introductionmentioning
confidence: 96%